Sociology of everyday life. (September 2013) - Kalekin-Fishman, Devorah
Everyday life has inspired much sociological theory and is now a recognized branch of the discipline. Here we trace evidence of the salience of everyday life in general sociological theory, look critically at theories specific to analyses of everyday life; then survey recent research. In closing, we look to the future of the field.